Temporal accumulation of salicylic acid activates the defense response against Colletotrichum in strawberry - Grellet Bournonville, Carlos Froilan (2012)
Many authors have reported interactions between strawberry cultivars and pathogenic microorganisms, yet little is known about the mechanisms triggered in the plant. In this paper we examine the participation of the salicylic acid (SA) signaling pathway involved in the response of Fragaria x ananassa cv. Pájaro plants to pathogens. Strawberry plants were challenged with the virulent strain M11 of Colletotrichum acutatum, or with the avirulent strain M23 of Colletotrichum fragariae which confers resistance to the former. Our study showed that the isolate M23 induced a temporal SA accumulation that was accompanied with the induction of PR- 1 gene expression in strawberry plants. Such events occured after the oxidative burst, evaluated as the accumulation of hydrogen peroxide and superoxide anion, and many hours before the protection could be detected. Similar results were obtained with exogenously applied SA. Results obtained supports the hypothesis that strawberry plants activate a SA mediated defense mechanisms that is effective against a causal agent of anthracnose. In contrast, plants inoculated with M11 did not show oxidative burst, SA accumulation or PR1 gene induction. This is the first report about a defense response signaling pathway studied in strawberry plants.